Proceedings of the International Conference on Strategic Issues of Economics, Business And, Education (ICoSIEBE 2020) 2021
DOI: 10.2991/aebmr.k.210220.029
|View full text |Cite
|
Sign up to set email alerts
|

Does the Implementation of Corporate Governance Moderate the Relationships of Ownership Structure, Capital Structure and Firm Values of Listed Manufacturing Companies in Indonesia?

Abstract: This study aims to examine corporate governance's role as a moderating variable in determining firm value, such as ownership structure and capital structure. Indonesian stock exchange manufacturing companies from 2014 to 2018 were used in this study. The data used was panel data, with data analysis carried out using the WarpPLS program. The results showed that the ownership structure had a significant effect on capital structure while ownership structure and capital structure had no significant effect on firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…It was observed that adding independent directors to the board has negatively changed the association between debt and firm performance, which is consistent with the empirical work of Abdulkarim and Bahamman (2021). In contrast to Mubaraq, Rahayu, Saifi, and Darmawan (2021), this study implies that increasing the control exercised by independent directors to reduce agency conflicts has an adverse impact on the relationship between debt and performance. This finding recommends that an efficient mix of independent directors to the total number of board members plays a crucial role, particularly in moderating the leverage and profitability association.…”
Section: Resultssupporting
confidence: 87%
“…It was observed that adding independent directors to the board has negatively changed the association between debt and firm performance, which is consistent with the empirical work of Abdulkarim and Bahamman (2021). In contrast to Mubaraq, Rahayu, Saifi, and Darmawan (2021), this study implies that increasing the control exercised by independent directors to reduce agency conflicts has an adverse impact on the relationship between debt and performance. This finding recommends that an efficient mix of independent directors to the total number of board members plays a crucial role, particularly in moderating the leverage and profitability association.…”
Section: Resultssupporting
confidence: 87%
“…Meanwhile, some other scholars believe that capital structure and firm performance have a more complex relationship [71][72][73][74][75][76]. It is not linear but possibly U-shaped, inverted U-shaped, or different for different indicators [71,[77][78][79][80], even with no links [81][82][83][84]. Furthermore, Table 1 summarizes the research findings on the relationship between capital structure and firm performance.…”
Section: Capital Structure and Firm Performancementioning
confidence: 99%
“…Positive [12, 56-59, 61, 85] Negative [4,[64][65][66][67][68][69][70] U-shaped [75,76] inverted U-shaped [17,[71][72][73][74]78] No links [43,[81][82][83][84] Different for different indicators [8,18,80,86] https://doi.org/10.1371/journal.pone.0306054.t001…”
Section: Capital Structure and Firm Performance Literaturementioning
confidence: 99%
“…However, previous studies have not tested this assertion. Mubaraq et al (2021) determined the moderating effect of corporate governance on the relationship between dividend and firm value. They found that a positive relationship exists between dividend policy and firm value.…”
Section: Interrelationship Between Board Structure Dividend Pay-out P...mentioning
confidence: 99%